Strengthening Transformational School Culture To Achieve School Excellence - Kemalahayati El Ahmady, Ratna; Sulisworo, Dwi; Hasanah, Enung (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to examine strategies for strengthening transformative school culture in achieving excellent schools within the Muhammadiyah educational environment A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed interactively using the Miles, Huberman, and Saldana model. The results show that the transformative school culture is implemented through the integration of Islamic values into daily school activities such as congregational prayers, Qur’anic recitation, and social programs like dawn charity and plastic donation. Strengthening strategies include transformative leadership, exemplary conduct, active involvement of school members, and partnerships with parents. Challenges encountered involve implementation inconsistency, limited resources, and resistance to change. Nevertheless, transformative culture has a positive impact on student character development, improvement of the learning climate, and increased public trust in the school. This study highlights the significance of transformative school culture as a foundation for building excellent Islamic value-based schools.